Caracterização dos reservatórios da bacia dos sertões de Crateús segundo a lei de segurança de barragens 12.334/2010 utilizando imagens de satélites - Sousa, Gleycianne Cavalcante Mariano de (2020)
The weirs play an important function in the water supply, specially in regions where the availability of this resource is limited, as it is in the brazilian northeast. There are reports that the land owners built these dams without the technical knowledge about the matter. The lack of information by the public authority about these barriers or about the current situation, result in a problem in fiscalization about the safety of these weirs. The law 12.334/2010 has the objective to assure that these structures meet the operational, structural and environmental aspects, seeking to avoid the occurrence of accidents and lessen the consequences throughout the lifespan of the building. This work presents a study upon the characterization of the earth dams of the Crateús Hinterlands Basin with the purpose to frame them in the law. The methodology constituted in using the water layers provided by the FUNCEME and identify through satellite images of Google Earth and the existence of earth dams. Of the 390 analysed layers 21 were natural reservoirs, 1 was a concrete dam, 86 water layers with the artificial aspect and 282 earth dams. With the use of the GIS tools (ArcGIS) information was obtained, like geographic localization, area and perimeter of the layers and the basin slope. Using those informations combined to simplified methodologies like the ones of Araújo et al. (2012) studies, it was possible to assess in practical means the heights and volumes of the 282 earth dams. For this method it was utilized a validation of results, as was used in Fernandes (2018) studies, that consists in parallel datas of heights and volumes of 10 known reservoirs with the estimations of this work. It was obtained a determination coefficient of 0,999 for the volumes and 0,992 for the dam heights, that means a satisfactory approximation of the real and estimated data for this basin. Lastly, it was made the framing of the dams according to the criteria in the law 12.334/2010. The analysed criteria was: the dams heights, the reservoir volumes and the verification of the weirs in relation to the Risk Category (CRI) and the Potential Associated Damage (DPA). This qualification of the reservoirs resulted that, of the 282 analysed earth dams, at least 55 are framed in some of the legislation determined criteria. It is concluded that of these 55 dams, 09 are monitored by the public authority and 46 are particular weirs that have no known information of their safety and maintenance.